2014
DOI: 10.1590/1678-775720140003
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of brachyfacial, mesofacial and dolichofacial individuals with regard to the buccal corridor in different facial types

Abstract: ObjectiveEvaluate the esthetic perception and attractiveness of the smile with regard to the buccal corridor in different facial types by brachyfacial, mesofacial and dolichofacial individuals.Material and MethodsThe image of a smiling individual with a mesofacial type of face was changed to create three different facial types with five different buccal corridors (2%, 10%, 15%, 22% and 28%). To achieve this effect, a photo editing software was used (Adobe Photoshop, Adobe Systems Inc, San Francisco, CA, EUA). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 18 publications
(31 reference statements)
0
12
0
Order By: Relevance
“…The rater's gender [ 16 , 30 ], age [ 9 ], education [ 9 ], self-perceived attractiveness [ 7 ], proficiency [ 32 ], and personal profile are influential in the scores of attractiveness. This needs to be considered while interpreting the results of our study; our participants were adult middle class participants and probably this limits our findings to this category…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rater's gender [ 16 , 30 ], age [ 9 ], education [ 9 ], self-perceived attractiveness [ 7 ], proficiency [ 32 ], and personal profile are influential in the scores of attractiveness. This needs to be considered while interpreting the results of our study; our participants were adult middle class participants and probably this limits our findings to this category…”
Section: Discussionmentioning
confidence: 99%
“…It had been suggested that dentists and laypeople (but not orthodontists) preferred 2 mm gingival display with short face, but for the long face the orthodontist preferred 0 mm gingival display, while the dentists and laypeople preferred 2 mm gingival display [ 6 ]. On another attempt, it is been found that individuals with different facial types had a different perception in what constitute an attractive smile when it comes to buccal corridors [ 7 ]; candidates with mesofacial, dolichofacial, and brachyfacial faces found the mesofacial face more attractive, accepting buccal corridors range from 2 to 15%. We believe that facial types (mesofacial, dolichofacial, and brachyfacial) are thought to play a role in facial esthetics.…”
Section: Introductionmentioning
confidence: 99%
“…9,16,17 Furthermore, in the literature, different judgments of smile attractiveness by different raters have been shown. 27,28,30,37 Some studies assessed in this regard 5 different sizes of BC (2%, 10%, 15%, 22%, and 28%) 17,35,36 and some others used 6 sizes (0%, 5%, 10%, 15%, 20%, and 25%). 30,37 In our study, we constructed only 3 sizes of BC (2%, 15% and 28%).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, regarding the facial type, some of the studies assessed just 2 facial types (short face and long face) 17 and some assessed 3 facial types. 36 We constructed 3 facial types (short face, normal face and long face) according to FI in order to compare smile attractiveness in each facial type.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation